Pengaruh Rasio Likuiditas, Leverage, Profitabilitas, dan Aktivitas terhadap Pertumbuhan Laba dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan Sektor Infrastructure periode 2020-2022 - Ardhana Putri, Saint Seiya; Paramita, R.A. Sista (Jurnal Ilmu Manajemen, 2025)
This study aims to determine the results of the analysis of the influence of liquidity proxied by the Current Ratio (CR), leverage proxied by the Debt to Equity Ratio (DER), profitability proxied by Return on Assets (ROA), and activity proxied by Total Asset Turnover (TATO) on profit growth with company size as a moderating variable in infrastructure sector companies. This study includes quantitative research with a population of infrastructure sector companies listed on the IDX for 2020-2022. The sampling method uses a purposive sampling method with a sample size of 162 samples from 54 companies. The data analysis technique uses the Moderated Regression Analysis (MRA) test. The results of the study show that the profitability ratio proxied by return on asset has a significant positive effect on profit growth. In contrast, other independent variables, such as liquidity, leverage, and activity, do not significantly affect profit growth. The moderation variable of company size can strengthen the influence of the profitability ratio on profit growth. However, company size cannot strengthen the influence of the liquidity ratio, leverage, and activity on profit growth. The implications of the research results show that Return on Asset (ROA) is very important for the growth of infrastructure company profits. Therefore, companies need to manage the assets they own so that they will increase company profits which will increase profit growth.